Cerebral perfusion measurement in brain death with intravoxel incoherent motion imaging. Issue 1 (December 2016) - Federau, Christian; Nguyen, Audrey; Christensen, Soren; Saba, Luca; Wintermark, Max
Abstract Background The assessment of brain death can be challenging in critically ill patients, and cerebral perfusion quantification might give information on the brain tissue viability. Intravoxel incoherent motion perfusion imaging is a magnetic resonance imaging technique, which extracts perfusion information from a diffusion-weighted sequence, and provides local, microvascular perfusion assessment without contrast media injection. Methods Diffusion weighted images were acquired with 16 b-values (0–900 s/mm2 ) in the brain in two patients with cerebral death, confirmed by clinical assessment and evolution, as well as in two age-matched healthy subjects. The intravoxel incoherent motion perfusion fraction maps were obtained by fitting the bi-exponential signal equation model. 8 regions of interest were drawn blindly in the brain neocortex (in the frontal, temporal, parietal, and occipital lobes on both sides) and perfusion fractions were compared between patients with cerebral death and healthy control. Statistical significance was assessed using two-sided Wilcoxon signed rank test, and set to α < 0.05. Results Intravoxel incoherent motion (IVIM) perfusion fraction was vanishing in the brain of the two patients with cerebral brain death compared to the healthy controls. Mean (± standard deviation) cortex perfusion fraction was 0.016 ± 0.005 respectively 0.005 ± 0.008 in the cerebral death patients, compared to respectively 0.052 ± 0.021 (p =  0.02) and 0.071 ± 0.042 (p =  0.008) in the age-matched controls. Conclusion Intravoxel incoherent motion perfusion imaging is a promising tool to assess local brain tissue viability in critically ill patients.